The elaboration of infographics about mining: in search of a contextualized Chemistry Teaching (Research, Society and Development, 2020)
This paper presents the study of metallic connections through mining and its social, economic and environmental impacts through the production of infographics. The objective of this work was to evaluate the production of infographics as a resource in the search for contextualization in Chemistry Teaching. The activities were developed with a class of thirty students of the first year of high school of a private school of the Municipality of Cachoeira do Sul, localized in State Rio Grande do Sul. The methodological path used was that of action research represented by a sequence of planning, implementation and evaluation of the results. The students were divided into groups, and chemical elements were raffle for the research and production of the infographics in which the images, texts, graphs and maps for their presentation were combined. The metals selected were according to the mining carried out in Brazil. The results indicate that the productions of the infographics made possible authorship process and creativity of the groups, of the ten works produced none of them met all the criteria requested, a possibility for this fact is the difficulty of carrying out the process of research, reading, interpretation and subsequent elaboration of the infographic. The students were able to build the infographics combining text with images, the activity motivated the participation and commitment of the groups that performed the use of infographics in other disciplines. The work made possible the conceptual approach of chemical connections in a contextualized way to the mining process, besides seeking to develop the students' view on the social aspects, economical and environmental providing a global and critical view on extraction processes.